COPD in primary lung cancer patients: prevalence and mortality - Ytterstad,Elinor; Moe,Per; Hjalmarsen,Audhild (International Journal of Chronic Obstructive Pulmonary Disease, 2016)
Elinor Ytterstad,1 Per C Moe,2 Audhild Hjalmarsen3 1Department of Mathematics and Statistics, UiT The Arctic University of Norway, 2Department of Pulmonary Medicine, University Hospital of North Norway, 3Department of Clinical Medicine, UiT The Arctic University of Norway, Tromsø, Norway Background: Previous studies have relied on international spirometry criteria to diagnose COPD in patients with lung cancer without considering the effect lung cancer might have on spirometric results. The aim of this study was to examine the prevalence of COPD and emphysema at the time of primary lung cancer diagnosis and to examine factors associated with survival. Materials and methods: Medical records, pulmonary function tests, and computed tomography scans were used to determine the presence of COPD and emphysema in patients diagnosed with primary lung cancer at the University Hospital of North Norway in 2008–2010. Results: Among the 174 lung cancer patients, 69% had COPD or emphysema (39% with COPD, 59% with emphysema; male:female ratio 101:73). Neither COPD nor emphysema were significantly associated with lung cancer mortality, whereas patients with non-small-cell lung cancer other than adenocarcinoma and squamous cell carcinoma had a risk of lung cancer mortality that was more than four times higher than that of patients with small-cell lung cancer (hazard ratio [HR] 4.19, 95% confidence interval [CI] 1.56–11.25). Females had a lower risk of lung cancer mortality than males (HR 0.63, 95% CI 0.42–0.94), and patients aged ≥75 years had a risk that was twice that of patients aged <75 years (HR 2.48, 95% CI 1.59–3.87). Low partial arterial oxygen pressure (4.0–8.4 kPa) increased the risk of lung cancer mortality (HR 2.26, 95% CI 1.29–3.96). So did low partial arterial carbon dioxide pressure (3.0–4.9 kPa) among stage IV lung cancer patients (HR 2.23, 95% CI 1.29–3.85). Several patients with respiratory failure had previously been diagnosed with COPD. Conclusion: The observed prevalence of COPD was lower than that in ...